2007
DOI: 10.1007/s10461-007-9265-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk and Bridging Behaviors Among Young People in Hai Phong, Vietnam

Abstract: The risk of the HIV epidemic spreading from high-risk groups to the general population in Vietnam depends on sexual risk and bridging behaviors between high- and low-risk individuals. A cross-sectional study was used to describe sexual activities of youth aged 18-29 years. Nearly half (41.4%) were sexually active. Premarital sex was reported by 43.3% of them; 78.3% of sexually active males and 13.5% of sexually active females. Multiple sex partners were reported by 31.0%; 56.7% of males and 9.2% of females. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 12 publications
5
32
1
Order By: Relevance
“…This study has suggested that those who reported multiple sex partners during the preceding years were less likely to use condoms consistently and more likely to engage in needle and syringe sharing behaviour. Several studies have reported sexual bridging behaviours between high risk groups and the general population (Duong et al 2008;Tran et al 2005;Tran et al 2006b). Our study suggested a high potential for HIV transmission from PLWHA to their sex partners through sexual mixing between groups.…”
Section: Discussionmentioning
confidence: 99%
“…This study has suggested that those who reported multiple sex partners during the preceding years were less likely to use condoms consistently and more likely to engage in needle and syringe sharing behaviour. Several studies have reported sexual bridging behaviours between high risk groups and the general population (Duong et al 2008;Tran et al 2005;Tran et al 2006b). Our study suggested a high potential for HIV transmission from PLWHA to their sex partners through sexual mixing between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, cultural influences have mitigated against premarital sex in young Vietnamese, but recently the prevalence of premarital sex in this cohort has been increasing (1,2). This places young individuals at increasing sexual and reproductive health risks.…”
Section: Introductionmentioning
confidence: 99%
“…This is partly because young people often have multiple partners (1). Moreover, many premarital sexual encounters involve HIV high-risk groups such as commercial sex workers (1).…”
Section: Introductionmentioning
confidence: 99%
“…While the damaging health consequences of homelessness in Vietnam have been studied previously (Duong et al, 2008), the health-seeking behaviors of young people living on the streets and their barriers to accessing health care services have remained poorly understood. This study seeks to contribute a greater understanding of health and health-seeking behavior among homeless youth in HCMC through our description of "protecting, balancing, and confronting".…”
Section: Resultsmentioning
confidence: 99%